Registros limnéticos de Hypanus sabinus (Myliobatiformes: Dasyatidae) en la cuenca del río Grijalva, sur del Golfo de México - Reyes-Ramírez, Henrry; Álvarez-Pliego, Nicolás; Sánchez, Alberto J.; Espinosa-Pérez, Héctor; Florido, Rosa; Salcedo, Miguel Ángel (Revista de Biología Marina y Oceanografía, 2019)
Hypanus sabinus is reported in the limnetic environments in the coastal plain of the Southern Gulf of Mexico. Eight specimens were collected 51 km away from the coastline in electric conductivity values less than 1,017 µS cm-1. One pregnant female and one male with two caudal spines are included. These findings represent the first limnetic records of this species in southern Mexico.